Evaluation method for wheel-rail contact mechanical properties based on volume ratio of pearlite and bainite
Patent Information
- Application Number
- CN202611517023.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-29
- Publication Date
- 2026-10-30
AI Technical Summary
①建立了珠光体与贝氏体体积比与轮轨接触力学性能之间的定量评估方法。本发明设置了多组(优选11组)珠光体与贝氏体体积比,覆盖从0%到100%的全成分区间。在此基础上,系统获得了接触法向力、法向应力、切向力及滑移等力学响应参数随体积比的完整演变规律。该结果弥补了双相材料微观组织与宏观接触性能之间定量关系研究不确定的缺陷。
Smart Images

Figure CN123013597A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of wheel-rail contact mechanics and material performance evaluation technology, and specifically relates to a wheel-rail contact mechanical performance evaluation method, which is a wheel-rail contact mechanical performance evaluation method based on the volume ratio of pearlite to bainite. Background Technology
[0002] Pearlite and bainite are the two most common microstructures in rail steel. The tensile strength is generally in the range of 800-1200 MPa, with good plasticity. Bainite consists of supersaturated ferrite and carbides, and its hardness is usually higher than that of pearlite, but its elongation after fracture and impact toughness are relatively lower. By adjusting the cooling rate and isothermal temperature during heat treatment, the relative content of these two phases in the steel can be changed, thus obtaining materials with different mechanical properties. The volume ratio of pearlite to bainite not only determines the macroscopic elastic modulus and yield strength of the material, but also directly affects its deformation behavior and damage evolution mechanism under high-stress cyclic loading conditions. The lamellar structure of pearlite endows the material with high tensile strength and good wear resistance, while the fine lath structure of bainite provides high hardness and a certain reserve of toughness. The complementary mechanical properties of the two phases give pearlite-bainite dual-phase steel a good matching advantage in hardness, strength, and toughness, but the realization of this advantage is highly dependent on the relative content and spatial distribution of the two phases. In practical engineering, the microstructure of rail materials often changes with fluctuations in heat treatment process parameters (such as cooling rate and isothermal temperature). This change is directly reflected in the two-phase volume ratio, thus affecting the mechanical response of the wheel-rail contact surface. Therefore, understanding the variation law of material mechanical properties under different volume ratios is of great significance for the stable control of rail quality.
[0003] The wheel-rail contact surface is subjected to extremely high normal loads and tangential frictional forces, with contact stresses reaching several GPa, sufficient to induce plastic deformation and fatigue damage. The microstructure of the material directly affects its performance under high-stress contact conditions. Therefore, clarifying how the volume ratio of pearlite and bainite influences wheel-rail contact mechanical behavior is of practical significance for rail composition design and heat treatment process formulation. Especially under the operating conditions of heavy-haul and high-speed railways, the wheel-rail contact stress level is further increased, and the regulatory role of microstructure on contact mechanical behavior is more significant. A systematic understanding of the quantitative relationship between the two has important engineering application value. The axle load of heavy-haul railways has increased from 25 tons to 30 tons or even higher, leading to a corresponding increase in contact stress and placing higher demands on the microstructure control of rail materials. Under different axle load conditions, the distribution and amplitude of contact stress vary, and the degree of influence of the material's microstructure on the contact response may also change accordingly.
[0004] For the problem of the inability to quickly correlate the microstructure parameters of wheel-rail materials with their macroscopic contact mechanical properties for evaluation, existing technologies have the following shortcomings: First, systematic research on the pearlite-bainite two-phase system across the entire composition range from 0% to 100% is still insufficient. Most studies focus on experimental tests at a few specific composition points, lacking continuous variation data covering the entire composition range. The evolution of contact force, stress distribution, and slip under different volume ratios remains incomplete. The variation patterns of fundamental mechanical parameters such as the equivalent elastic modulus and Poisson's ratio under different volume ratios lack systematic characterization, directly hindering the rational selection of material constitutive parameters in wheel-rail contact finite element simulations. Furthermore, the equivalent elastic modulus, as one of the most important input parameters in finite element simulations, directly affects the calculation accuracy of contact stress, strain, and deformation fields. However, existing research lacks a systematic report on the quantitative relationship between the equivalent elastic modulus of pearlite-bainite two-phase materials and their variation with volume ratio, and the applicability of the Voigt mixing rule in this system lacks sufficient verification. Relying solely on empirical values or extrapolation from single-point experimental data makes it difficult to guarantee the reliability of contact calculation results under different volume ratios.
[0005] Secondly, in finite element simulations of wheel-rail contact, rail materials are typically treated as homogeneous bodies, directly using mechanical parameters with a fixed composition, without fully considering the quantitative impact of changes in the two-phase ratio in the actual rail on the contact calculation results. This leads to a lack of basis for material selection in simulations. For rails of different grades or different heat treatment batches, their pearlite content may vary significantly, but existing simulation models lack effective parameterization methods to describe this difference. They usually have to use the same set of material parameters for calculations, failing to reflect the influence of the actual microstructure on contact mechanical behavior.
[0006] Third, the difference in mechanical properties between the two phases can lead to strain incompatibility at the phase interface. How this localized effect maps to the macroscopic response of the wheel-rail contact interface, such as the magnitude of contact force, slip direction, and amplitude, remains unclear. The degree of stress-strain concentration at the two-phase interface is closely related to the volumetric composition, but existing research is mostly limited to qualitative descriptions, lacking computational models that can quantitatively describe this relationship. Under contact loads, the deformation difference between the soft and hard phases may lead to interface debonding or microcrack initiation. How this microscopic damage affects macroscopic contact performance is currently lacking in systematic quantitative research.
[0007] Fourth, existing research lacks a systematic evaluation method for assessing the transition from microscopic constitutive parameters to macroscopic contact response. After obtaining the microstructure parameters of materials, the lack of a complete simulation evaluation process for quickly and accurately assessing their impact on wheel-rail contact mechanics limits the effective connection between the microstructure design and macroscopic service performance of wheel-rail materials. Due to the lack of a standardized evaluation process, different researchers use different constitutive models, boundary conditions, and evaluation indicators, resulting in a lack of comparability between results. Establishing a standardized evaluation process would make the results from different material systems and under different research conditions comparable, which is of great significance for promoting the development of the field of wheel-rail contact mechanics.
[0008] Relevant patent document CN121682157A discloses a wheel-rail contact state assessment method based on logistic regression. Based on wheel-rail contact theory, it selects the percentage of contact point distribution, concentration composite index, and 3mm equivalent taper as multi-dimensional parameters to more comprehensively and accurately characterize the wheel-rail contact state, avoiding assessment bias caused by parameter bias, and making the level assessment results more consistent with the actual wheel-rail matching performance. Furthermore, it adopts a logistic regression model as the core algorithm for assessment. The mapping relationship between the model input and output can be quantitatively explained through regression coefficients. The model has strong interpretability, adapts to engineering practice needs, and the model threshold can be flexibly adjusted according to the operation and maintenance needs of different lines to avoid potential safety risks and adapt to diverse railway operation scenarios.
[0009] The above technologies do not solve the problem in existing technologies where, after obtaining the microstructure parameters of the wheel and rail materials, the microstructure parameters of the wheel and rail materials cannot be quickly correlated with the macroscopic contact mechanical properties of the wheel and rail for evaluation. Summary of the Invention
[0010] The purpose of this invention is to provide a method for evaluating the mechanical properties of wheel-rail contact based on the volume ratio of pearlite to bainite. After obtaining the microstructure parameters of the wheel-rail materials, this method can quickly and accurately evaluate the influence of the microstructure on the mechanical properties of wheel-rail contact, thereby solving the problem that the microstructure parameters of wheel-rail materials cannot be quickly correlated with the macroscopic mechanical properties of wheel-rail contact for evaluation.
[0011] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: A method for evaluating the mechanical properties of wheel-rail contact based on the volume ratio of pearlite to bainite, comprising the following steps: S1: For the pearlite and bainite in wheel and rail materials, multiple sets of pearlite and bainite volume ratios are set.
[0012] S2: Determine the material parameters.
[0013] S3: Calculate the equivalent elastic parameters for each group of volume ratios according to Voigt's constant strain mixing principle. The equivalent elastic parameters include the equivalent elastic modulus. and equivalent Poisson ratio The above-mentioned mixing rule is based on the assumption of equal strain and is applicable to two-phase material systems with good interfacial bonding and good deformation compatibility. It is a method for calculating the equivalent elastic properties of two-phase materials.
[0014] S4: Establish a finite element model of the dumbbell-shaped uniaxial tensile specimen and perform tensile simulation verification: Assign the equivalent elastic parameters under each volume ratio obtained in step S3 to the first model, obtain the stress-strain curves under each volume ratio, and verify the prediction accuracy of the hybrid rule in the elastic stage; extract the data from the stress-strain curves and perform linear fitting to obtain the simulated values of the equivalent elastic modulus under each volume ratio, and compare each simulated value of the equivalent elastic modulus with the corresponding equivalent elastic modulus in step S3. If the relative deviation is ≤X when comparing with the theoretical value, proceed to the next step; otherwise, return to check the parameters and model settings and re-verify.
[0015] S5: Establish a three-dimensional finite element model of wheel-rail contact; assign the simulated values of the equivalent elastic modulus (equivalent elastic parameters of each group) under the volume ratios compared in step S4 and the plastic parameters determined by linear interpolation according to the mixing rule to the rail material in the model; perform wheel-rail contact simulation.
[0016] S6: Extract the mechanical response parameters on the wheel-rail contact interface and obtain the variation characteristics of each mechanical response parameter with the volume fraction of pearlite.
[0017] S7: Based on the variation characteristics of each mechanical response parameter with the pearlite volume fraction, determine the evolution stage of wheel-rail contact mechanical properties: when Performance is stable when ≤50%; when 60%≤ Performance changes drastically when ≤80%; Performance stabilizes when ≥85% is achieved; This represents the volume fraction of pearlite.
[0018] In the above technical solution, a preferred approach is to set 11 sets of pearlite to bainite volume ratios in step S1. These 11 sets of pearlite to bainite volume ratios are: 0:10, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, 9:1, and 10:0. These 11 sets of pearlite to bainite volume ratios cover the complete compositional range from all bainite to all pearlite, with a step size of 10%, which is sufficient to reflect the influence trend of continuous changes in the two-phase ratio on the material's mechanical properties. The 11 sets of pearlite to bainite volume ratio data constitute a full compositional scan, which can systematically identify performance abrupt change ranges and avoid missing critical volume ratios due to excessively large step sizes.
[0019] In step S2, the material parameters include the elastic modulus of pearlite. Pearl Poisson's ratio bainitic elastic modulus Bausch's Poisson's ratio .
[0020] The numerical values of the material parameters can be: pearlitic elastic modulus =206.3 GPa, Pearlite Poisson's Ratio =0.2885, bainitic elastic modulus =184.5 GPa, Bausch's Poisson's ratio =0.314. Material parameters may also include values from the yield stress vs. plastic strain curves for pearlite and bainite.
[0021] In step S3, the equivalent elastic modulus and equivalent Poisson ratio The calculation formula is: (1), (2), in, This represents the volume fraction of pearlite. is the volume fraction of bainite, and .
[0022] In step S4, the total length of the dumbbell-shaped uniaxial tensile specimen (i.e., the dumbbell-shaped specimen) is 300 mm, the length of the gauge length is 80 mm, the diameter of the clamping end is 60 mm, the diameter of the gauge length is 35 mm, and the fillet radius at the rounded transition area is 106 mm. The mesh is generated using C3D8R eight-node hexahedral linear reduced integral elements, with local refinement in the central region of the gauge length. The total number of elements is 10,000-12,000, and the total number of elements can be selected as 12,000. The method for extracting data from the stress-strain curves and performing linear fitting to obtain the simulated equivalent elastic modulus values for each volume ratio is as follows: Using a displacement loading method, the lower end face of the specimen is fixed, and a tensile load with a total displacement of 12 mm and a loading rate of 2 mm / min is applied axially to the upper end face of the specimen. The stress-strain data at the center node of the gauge length segment in the stress-strain curve is extracted and linearly fitted to obtain the simulated equivalent elastic modulus values for each volume ratio. The peak stress at the center node of the gauge length segment is 37.9~42.4 MPa, accounting for only 6.5%~10.8% of the yield strength, and all conditions are in the linear elastic deformation stage. The dumbbell-shaped specimen is the standard form for uniaxial tensile testing of materials, and its gauge length segment is a uniform stress zone. The stress-strain data at the center node can accurately reflect the constitutive response of the material.
[0023] In step S4, when displacement loading is used, the ratio of kinetic energy to internal energy is always ≤5% during the loading process, satisfying the quasi-static loading condition. In step S4, X = 0.01%.
[0024] In the above technical solution, a preferred technical solution is that, in step S5, the three-dimensional finite element model of wheel-rail contact includes wheelsets, frames, outer rails, inner rails, floating plates, fasteners, primary suspension, grounding springs, and track bed. The wheelsets consist of an outer wheel, an inner wheel, and an axle. The outer and inner rails are two steel rails. The wheel-rail system is composed of wheels (outer and inner wheels) and rails (outer and inner rails). The method for simulating wheel-rail contact is to use the surfaces of the outer and inner wheels as the master surfaces, and the surfaces of the outer and inner rails as slave surfaces. A finite slip formula is used, the normal contact behavior is tight contact (i.e., "hard" contact), and the tangential behavior uses a penalty function friction formula. The friction coefficient is taken as 0.35 based on typical steel-steel contact characteristics.
[0025] The three-dimensional finite element model of wheel-rail contact fully reflects the actual force transmission path of the wheel-rail system: the wheel-rail contact force is transmitted to the bogie frame through the primary suspension, and then to the car body through the secondary suspension. The fasteners and floating plates then transmit the wheel-rail contact force to the bogie frame. Rail forces are transmitted to the track bed. Assigning equivalent elastoplastic parameters to the rail material allows for the simulation of differences in wheel-rail contact response under different microstructures. In wheel-rail contact simulation, the constitutive parameters of the rail material directly affect the stress distribution and plastic strain accumulation within the contact patch. Assigning equivalent elastoplastic parameters corresponding to different volume ratios to the rail material allows for a quantitative assessment of the impact of microstructure differences on the macroscopic response of wheel-rail contact. The friction coefficient is determined with reference to experimental data from typical steel-steel contacts to ensure the simulation results are comparable to engineering realities.
[0026] In step S5, the parameters of the primary suspension are: vertical stiffness is 1.30 × 10⁻⁶. 6 N / m, lateral stiffness is 1.10×10 6 N / m, longitudinal stiffness is 1.10×10 6 N / m, vertical damping is 5.00×10 3 N·s / m; The parameters of the fastener body are: vertical stiffness is 4.07×10 N·s / m. 7 N / m, lateral stiffness is 8.79×10 6 N / m, longitudinal stiffness is 8.79×10 6 N / m, vertical damping is 9.898×10 3 N·s / m, lateral damping is 1.928×10 3 N·s / m, longitudinal damping is 1.928×10 3 The strength of the steel spring vibration isolators in the floating slab is N·s / m, with a spacing of 0.60m; the parameters are: vertical stiffness is 5.33×10⁻⁶. 6 N / m, lateral stiffness is 4.56×10 6 N / m, longitudinal stiffness is 4.56×10 6 N / m, vertical damping is 1.50×10 4 N·s / m, lateral damping is 1.00×10 4 N·s / m, longitudinal damping is 1.00×10 4 The strength of the bogie is N·s / m, the spacing is 1.20m, and the wheelbase is 2.50m.
[0027] In step S5, the material of the rail inside the model is elastoplastic constitutive and isotropically hardened.
[0028] In step S6, the mechanical response parameters include contact normal force CNORMF, contact normal stress CPRESS, transverse shear stress CSHEAR1, longitudinal shear stress CSHEAR2, combined tangential force CSHEARF, transverse slip CSLIP1, and longitudinal slip CSLIP2; and the equivalent coefficient of friction at each volume ratio. =CSHEARF max / CNORMFmax All of these parameters fall within the range of 0.350 to 0.351. These parameters cover the mechanical behavior of the wheel-rail contact interface in three aspects: normal force, tangential friction, and relative slippage, forming a complete contact mechanics evaluation index system.
[0029] In the above technical solution, a preferred technical solution may also be that, in step S7, the microscopic mechanism of the sudden change in performance is: pearlite volume fraction When the content is 70%, the hard phase pearlite tends to form a continuous load-bearing skeleton. The deformation and incoordination between the pearlite and bainite phases intensify, leading to a sudden change in contact mechanical properties.
[0030] In step S7, the specific manifestation of the sudden change in performance is: in the pearlite volume fraction At 70%, the contact normal force CNORMF decreases from 1.178 × 10⁻⁶. 4 N decreased to 6.524 × 10 3 N decreased by 44.6%; the contact normal stress CPRESS decreased from 15.44 MPa to 8.551 MPa, a decrease of 44.6%; the transverse shear stress CSHEAR1 increased from ±0.11 MPa to ±0.17 MPa, an increase of 50%; the absolute value of the longitudinal shear stress CSHEAR2 decreased from 5.40 MPa to 2.99 MPa, a decrease of 44.7%; the combined tangential force CSHEARF decreased from 4.128 × 10⁻⁶ MPa. 3 N decreased to 2.287 × 10 3 N decreased by 44.6%; the amplitude of lateral slip CSLIP1 decreased from 0.075 mm to 0.050 mm, a reduction of 33%; the longitudinal slip CSLIP2 reversed from being dominated by positive (+0.295~0.000 mm) to being dominated by negative (+0.061~-0.273 mm).
[0031] The method for evaluating the mechanical properties of wheel-rail contact based on the volume ratio of pearlite to bainite preferably further includes the following steps: S8: After step S7, determine the design criterion output step, i.e., when the engineering application requires stable contact mechanical properties, select... ≤50% or ≥85%, avoid 60%≤ The critical sensitivity range is ≤80%. This represents the volume fraction of pearlite.
[0032] This invention is implemented using ABAQUS finite element software and employs Python scripts for parametric modeling and batch simulation calculations.
[0033] This invention addresses the lack of quantitative evaluation methods for the relationship between the volume ratio of pearlite to bainite in wheel-rail materials and their contact mechanical properties. It studies multiple groups (preferably 11 groups) of different pearlite to bainite volume ratios (from 0:10 to 10:0). First, the equivalent elastic modulus and equivalent Poisson's ratio for each group are calculated using the Voigt equal strain mixing method. A dumbbell-shaped uniaxial tensile specimen finite element model is then established for tensile simulation, obtaining stress-strain curves for each volume ratio to verify the prediction accuracy of the mixing method in the elastic stage. Then, the verified equivalent elastoplastic parameters are assigned to the three-dimensional finite element model of wheel-rail contact, and wheel-rail contact simulation is performed. The normal force, tangential force, and slip on the contact surface are extracted as evaluation indicators. Analysis results show that the stress-strain curves are highly linear at all volume fractions, and the equivalent elastic modulus increases linearly from 184.5 GPa to 206.3 GPa with increasing pearlite content. The contact normal force and normal stress exhibit non-monotonic evolution with pearlite content; a critical abrupt change occurs when the pearlite volume fraction reaches 70%, resulting in a sharp drop of 44.6% in the contact normal force, a 50% increase in transverse shear stress, a 44.7% decrease in the absolute value of longitudinal shear stress, a decrease in transverse slip amplitude of approximately 33%, and a reversal in the longitudinal slip direction. The equivalent friction coefficient remains stable between 0.350 and 0.351 at all volume fractions, unaffected by the microstructure ratio. This invention clarifies that a pearlite volume fraction of 60%–80% represents the critical sensitive range for wheel-rail contact mechanical properties. Material design should ensure that the pearlite content (i.e., pearlite volume fraction) is ≤50% or ≥85% to avoid this unstable range. This invention eliminates the need for extensive experimental testing, enabling rapid correlation assessment of the microstructure parameters and macroscopic contact mechanical properties of wheel-rail materials solely through finite element simulation. It can be widely applied to component screening and heat treatment process optimization during the wheel-rail material development stage. This method is also suitable for comparative evaluation of the contact mechanical properties of wheel-rail materials under different steel grades and heat treatment conditions, providing a universal simulation analysis tool for rail material design.
[0034] This invention proposes a complete evaluation process from single-phase parameter input to contact response output, establishing the correspondence between volume ratio and contact performance using finite element analysis; it can identify the critical volume ratio range where contact mechanical properties undergo abrupt changes; and it elucidates the microscopic mechanism by which changes in the microstructure volume ratio lead to abrupt changes in macroscopic contact mechanical properties. The beneficial effects of employing the above-mentioned technical solution of this invention are as follows: ① A quantitative evaluation method was established for the relationship between the volume ratio of pearlite to bainite and the mechanical properties of wheel-rail contact. This invention sets multiple (preferably 11) pearlite to bainite volume ratios, covering the entire composition range from 0% to 100%. Based on this, the complete evolution law of mechanical response parameters such as contact normal force, normal stress, tangential force, and slippage as a function of volume ratio was obtained systematically. This result overcomes the deficiency in the study of the uncertain quantitative relationship between the microstructure and macroscopic contact properties of dual-phase materials.
[0035] ② It was identified that a pearlite volume fraction of 60%–80% represents a critical sensitive range for the mechanical properties of wheel-rail contact. This invention proposes that when the pearlite content is around 70%, a series of critical phenomena occur, such as a sharp drop of 44.6% in the contact normal force, a 50% increase in the transverse shear stress, and a reversal of the longitudinal slip direction. This clarifies that this range is a sensitive area for unstable material properties, providing a clear avoidance criterion for the microstructure design of wheel-rail materials.
[0036] ③ A complete simulation evaluation process from uniaxial tensile constitutive characterization to wheel-rail contact response was established. This invention obtains the elastic constitutive parameters for each volume ratio using tensile simulation of a dumbbell-shaped uniaxial tensile specimen, and then assigns the elastoplastic parameters to the wheel-rail contact model for subsequent analysis. This achieves a full-chain simulation evaluation from material constitutive model to macroscopic contact response, without relying on extensive experimental testing, resulting in high computational efficiency and strong repeatability. Each step in this process has clearly defined inputs, outputs, and judgment criteria, making it highly operable. The results obtained by different researchers using this method show good consistency. This evaluation process uses finite element simulation, which can significantly reduce experimental costs and shorten the material evaluation cycle.
[0037] ④ This invention reveals the microscopic mechanism by which changes in the volume ratio of microstructure lead to abrupt changes in macroscopic contact mechanical properties. From the perspective of two-phase deformation incompatibility, this invention elucidates the mechanism by which changes in the volume fraction of pearlite... The fundamental reason for the sudden change in mechanical properties at 70% is the stress concentration and deformation incoordination at the interface between the hard and soft phases caused by the formation of a continuous network of hard pearlite.
[0038] ⑤ This study verified that the equivalent friction coefficient is independent of the microstructure composition. The present invention proposes that the equivalent friction coefficient remains stable between 0.350 and 0.351 for all volume ratios, confirming that the friction coefficient is determined by the characteristics of the contact interface.
[0039] ⑥ The high accuracy (relative deviation ≤ 0.01%) of Voigt's equal strain mixing rule in predicting the elastic modulus of pearlite / bainite dual-phase materials was verified, providing a scientific basis for the selection of constitutive parameters of dual-phase materials in finite element simulation.
[0040] In summary, this invention provides a method for evaluating the mechanical properties of wheel-rail contact based on the volume ratio of pearlite to bainite. After obtaining the microstructure parameters of the wheel-rail materials, it can quickly and accurately assess the influence of the microstructure on the mechanical properties of wheel-rail contact, solving the problem that the microstructure parameters of wheel-rail materials cannot be quickly correlated with the macroscopic mechanical properties of wheel-rail contact. This invention is applicable to the component screening and constitutive parameter selection in finite element modeling during the wheel-rail material development stage. It is also applicable to the comparative evaluation of the mechanical properties of wheel-rail materials under different heat treatment processes. It provides a method for studying the correlation between the microstructure design and service performance optimization of rail materials. This method can also be used to analyze the differences in wheel-rail contact fatigue life under different pearlite to bainite volume ratios, providing a basis for extending the service life of rails. Attached Figure Description
[0041] Figure 1 This is a flowchart (block diagram) of the overall invention.
[0042] Figure 2 This is a flowchart of the wheel-rail contact mechanical performance evaluation method based on the volume ratio of pearlite to bainite according to Embodiment 1 of the present invention.
[0043] Figure 3 This is a finite element model of the dumbbell-shaped uniaxial tensile specimen described in this invention, and a schematic diagram of the two-phase distribution of pearlite and bainite, taking a pearlite to bainite volume ratio of 7:3 as an example. Figure 3 White represents pearlite, and green represents bainite.
[0044] Figure 4 , Figure 5 This is a schematic diagram of the three-dimensional finite element model of wheel-rail contact described in this invention. Figure 4 This is a diagram showing the overall structure and component composition of the three-dimensional finite element model. Figure 5 This is a cross-sectional view of the three-dimensional finite element model at the wheel-rail position.
[0045] Figure 6 The stress-time curves of the center node under different volume ratios in the experiment of this invention are shown.
[0046] Figure 7 The strain-time curves of the center node under different volume ratios in the experiment of this invention are shown.
[0047] Figure 8 , Figure 9 , Figure 10 This is a CNORMF contour map of the contact normal force under three different pearlite contents in the experiments of this invention. Figure 8 CNORMF contour plot of the contact normal force when the pearlite content is 0%. Figure 9 CNORMF contour plot of the contact normal force when the pearlite content is 70%. Figure 10 This is a contour plot of the contact normal force CNORMF when the pearlite content is 100%.
[0048] Figure 11 , Figure 12 , Figure 13 This is a CPRESS contour plot of the contact normal stress of pearlite under three different contents in the experiments of this invention. Figure 11 This is a CPRESS contour plot of the contact normal stress when the pearlite content is 0%. Figure 12 This is a CPRESS contour plot of the contact normal stress when the pearlite content is 70%. Figure 13 This is a CPRESS contour plot of the contact normal stress when the pearlite content is 100%.
[0049] Figure 14 , Figure 15 , Figure 16 This is a CSHEAR1 contour plot showing the transverse shear stress of pearlite under three different content conditions in the experiments of this invention. Figure 14 The image shows the CSHEAR1 contour plot of the transverse shear stress when the pearlite content is 0%. Figure 15 The image shows the CSHEAR1 contour plot of the transverse shear stress when the pearlite content is 70%. Figure 16 The image shows the transverse shear stress CSHEAR1 contour plot when the pearlite content is 100%.
[0050] Figure 17 , Figure 18 , Figure 19 This is a CSHEAR2 contour plot of the longitudinal shear stress of pearlite under three different contents in the experiments of this invention. Figure 17 The image shows the CSHEAR2 contour plot of the longitudinal shear stress when the pearlite content is 0%. Figure 18 The image shows the CSHEAR2 contour plot of the longitudinal shear stress when the pearlite content is 70%. Figure 19 The image shows the CSHEAR2 contour plot of the longitudinal shear stress when the pearlite content is 100%.
[0051] Figure 20 , Figure 21 , Figure 22 This is a CSHEARF contour map of the synthetic tangential force of pearlite under three different content conditions in the experiment of this invention. Figure 20 The CSHEARF contour plot shows the synthetic tangential force when the pearlite content is 0%. Figure 21 The CSHEARF contour plot shows the synthetic tangential force when the pearlite content is 70%. Figure 22 The CSHEARF contour plot shows the synthetic tangential force when the pearlite content is 100%.
[0052] Figure 23 , Figure 24 , Figure 25 This is a CSLIP1 contour map showing the lateral slip of pearlite under three different content conditions in the experiments of this invention. Figure 23 The image shows the lateral slip CSLIP1 contour plot when the pearlite content is 0%. Figure 24 The image shows the lateral slip CSLIP1 contour plot when the pearlite content is 70%. Figure 25 The image shows the lateral slip CSLIP1 contour plot when the pearlite content is 100%.
[0053] Figure 26 , Figure 27 , Figure 28 This is a CSLIP2 contour map showing the longitudinal slip of pearlite under three different content conditions in the experiments of this invention. Figure 26 This is a CSLIP2 contour plot showing the longitudinal slip when the pearlite content is 0%. Figure 27 This is a CSLIP2 contour map showing the longitudinal slip when the pearlite content is 70%. Figure 28 The image shows the longitudinal slip CSLIP2 contour plot when the pearlite content is 100%. Detailed Implementation
[0054] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. Based on these embodiments, all other embodiments obtained by those skilled in the art without creative effort are within the scope of this invention.
[0055] Example 1: As Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 , Figure 6 , Figure 7 As shown, the wheel-rail contact mechanical performance evaluation method based on the volume ratio of pearlite to bainite of the present invention includes the following steps: S1: For the pearlite and bainite in wheel and rail materials, multiple sets of pearlite and bainite volume ratios are set.
[0056] In step S1, 11 sets of pearlite to bainite volume ratios are set, with the following values: 0:10, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, 9:1, and 10:0. These 11 sets of pearlite to bainite volume ratios cover the complete compositional range from all-bainite to all-pearlite, with a step size of 10%, sufficient to reflect the influence of continuous changes in the two-phase ratio on the material's mechanical properties. These 11 sets of pearlite to bainite volume ratio data constitute a full compositional scan, which can systematically identify performance abrupt change ranges and avoid missing critical volume ratios due to excessively large step sizes.
[0057] S2: Determine the material parameters, including the elastic modulus of pearlite. Pearl Poisson's ratio bainitic elastic modulus Bausch's Poisson's ratio .
[0058] In step S2, the elastic modulus of pearlite =206.3 GPa, Pearlite Poisson's Ratio =0.2885, bainitic elastic modulus =184.5 GPa, Baustenite Poisson's ratio =0.314. Material parameters also include values from the yield stress vs. plastic strain curves for pearlite and bainite.
[0059] S3: Calculate the equivalent elastic parameters for each group of volume ratios according to Voigt's constant strain mixing principle. The equivalent elastic parameters include the equivalent elastic modulus. and equivalent Poisson ratio Equivalent elastic modulus and equivalent Poisson ratio The calculation formula is: (1), (2), in, This represents the volume fraction of pearlite. is the volume fraction of bainite, and .
[0060] The above-mentioned mixing rule is based on the assumption of equal strain and is applicable to two-phase material systems with good interfacial bonding and good deformation compatibility. It is a classic method for calculating the equivalent elastic properties of two-phase materials.
[0061] S4: Establish a finite element model of the dumbbell-shaped uniaxial tensile specimen and perform tensile simulation verification: Assign the equivalent elastic parameters under each volume ratio obtained in step S3 to the first model, obtain the stress-strain curves under each volume ratio, and verify the prediction accuracy of the hybrid rule in the elastic stage; extract the data from the stress-strain curves and perform linear fitting to obtain the simulated values of the equivalent elastic modulus under each volume ratio, and compare each simulated value of the equivalent elastic modulus with the corresponding equivalent elastic modulus in step S3. Compare with theoretical values. If the relative deviation is ≤X, proceed to the next step, where X=0.01%; otherwise, return to check the parameters and model settings and re-verify.
[0062] In step S4, the total length of the dumbbell-shaped uniaxial tensile specimen (dumbbell-shaped specimen) is 300 mm, the length of the gauge length 102 is 80 mm, the diameter of the clamping end 101 is 60 mm, the diameter of the gauge length 102 is 35 mm, and the radius of the fillet at the rounded transition area 103 is 106 mm. The mesh is generated using C3D8R eight-node hexahedral linear reduced integral elements, and the central area of the gauge length 102 is locally refined. The total number of elements is 10,000-12,000, and 12,000 elements are selected in this embodiment. The method for extracting data from the stress-strain curves and performing linear fitting to obtain the simulated equivalent elastic modulus values for each volume ratio is as follows: Using a displacement loading method, the lower end face of the specimen is fixed, and a tensile load with a total displacement of 12 mm and a loading rate of 2 mm / min is applied axially to the upper end face of the specimen. The stress-strain data at the center node of gauge length segment 102 in the stress-strain curves are extracted and linearly fitted to obtain the simulated equivalent elastic modulus values for each volume ratio. The peak stress at the center node of gauge length segment 102 is 37.9~42.4 MPa, accounting for only 6.5%~10.8% of the yield strength, and all conditions are in the linear elastic deformation stage. The dumbbell-shaped specimen is the standard form for uniaxial tensile testing of materials, and its gauge length segment 102 is a uniform stress zone; the stress-strain data at the center node can accurately reflect the constitutive response of the material.
[0063] In step S4, when the displacement loading method is used, the ratio of kinetic energy to internal energy is always ≤5% during the loading process, which satisfies the quasi-static loading condition.
[0064] S5: Establish a three-dimensional finite element model of wheel-rail contact; assign the simulated values of the equivalent elastic modulus (equivalent elastic parameters of each group) under the volume ratios compared in step S4 and the plastic parameters determined by linear interpolation according to the mixing rule to the rail material in the model; perform wheel-rail contact simulation.
[0065] In step S5, the three-dimensional finite element model of the wheel-rail contact includes wheelset 201, frame 202, outer rail 203a, inner rail 203b, floating plate 204, fastener 205, primary suspension 206, grounding spring 207, and track bed 208. Wheelset 201 consists of outer wheel 201a, inner wheel 201b, and axle 201c. Outer rail 203a and inner rail 203b are two steel rails. Wheel-rail 209 is a system composed of wheels (outer wheel 201a and inner wheel 201b) and steel rails (outer rail 203a and inner rail 203b). The method for simulating wheel-rail contact is to use the surfaces of the outer wheel 201a and the inner wheel 201b as the main surfaces, and the surfaces of the outer rail 203a and the inner rail 203b as the secondary surfaces. The finite slip formula is used, the normal contact behavior is tight contact, i.e., "hard" contact, and the tangential behavior adopts the penalty function friction formula. The friction coefficient is taken as 0.35 according to the typical steel-steel contact characteristics.
[0066] The three-dimensional finite element model of wheel-rail contact fully reflects the actual force transmission path of the wheel-rail system: the wheel-rail contact force is transmitted to the bogie frame 202 through the primary suspension 206, and then to the car body through the secondary suspension. The fasteners 205 and the floating plate 204 transmit the wheel-rail force to the track bed 208. Assigning equivalent elastoplastic parameters to the rail material allows for the simulation of differences in wheel-rail contact response under different microstructures. In wheel-rail contact simulation, the constitutive parameters of the rail material directly affect the stress distribution and plastic strain accumulation within the contact patch. Assigning equivalent elastoplastic parameters corresponding to different volume ratios to the rail material allows for a quantitative assessment of the influence of microstructure differences on the macroscopic response of wheel-rail contact. The friction coefficient is determined with reference to experimental data from typical steel-steel contacts to ensure the simulation results are comparable to engineering realities.
[0067] In step S5, the parameters of the primary suspension 206 are: vertical stiffness is 1.30 × 10⁻⁶. 6 N / m, lateral stiffness is 1.10×10 6 N / m, longitudinal stiffness is 1.10×10 6 N / m, vertical damping is 5.00×10 3 N·s / m; The parameters of the fastener 205 body are: vertical stiffness is 4.07×10 N·s / m. 7 N / m, lateral stiffness is 8.79×10 6 N / m, longitudinal stiffness is 8.79×10 6 N / m, vertical damping is 9.898×10 3 N·s / m, lateral damping is 1.928×10 3 N·s / m, longitudinal damping is 1.928×10 3The strength of the steel spring vibration isolators in the floating slab 204 is N·s / m, with a spacing of 0.60m; the parameters are: vertical stiffness is 5.33×10 N·s / m. 6 N / m, lateral stiffness is 4.56×10 6 N / m, longitudinal stiffness is 4.56×10 6 N / m, vertical damping is 1.50×10 4 N·s / m, lateral damping is 1.00×10 4 N·s / m, longitudinal damping is 1.00×10 4 The N·s / m and the spacing is 1.20m; the wheelbase of the bogie is 2.50m. The secondary suspension, car body and bogie are not shown in the attached drawings.
[0068] In step S5, the material of the rail inside the model is elastoplastic constitutive and isotropically hardened.
[0069] S6: Extract the mechanical response parameters on the wheel-rail contact interface and obtain the variation characteristics of each mechanical response parameter with the volume fraction of pearlite.
[0070] In step S6, the mechanical response parameters include contact normal force CNORMF, contact normal stress CPRESS, transverse shear stress CSHEAR1, longitudinal shear stress CSHEAR2, combined tangential force CSHEARF, transverse slip CSLIP1, and longitudinal slip CSLIP2; and the equivalent coefficient of friction for each group of volume ratios. =CSHEARF max / CNORMF max All are within the range of 0.350 to 0.351.
[0071] The above parameters cover the mechanical behavior of the wheel-rail contact interface in three aspects: normal force, tangential friction, and relative slippage, forming a complete contact mechanics evaluation index system.
[0072] S7: Based on the variation characteristics of each mechanical response parameter with the pearlite volume fraction, determine the evolution stage of wheel-rail contact mechanical properties: when Performance is stable when ≤50%; when 60%≤ Performance changes drastically when ≤80%; Performance stabilizes when ≥85% is achieved.
[0073] In step S7, the microscopic mechanism by which the performance undergoes a sudden change is as follows: When the content is 70%, the hard phase pearlite tends to form a continuous load-bearing skeleton. The deformation and incoordination between the pearlite and bainite phases intensify, leading to a sudden change in contact mechanical properties.
[0074] In step S7, the specific manifestation of the sudden performance change is as follows: At 70%, the contact normal force CNORMF decreases from 1.178 × 10⁻⁶. 4 N decreased to 6.524 × 10 3 N decreased by 44.6%; the contact normal stress CPRESS decreased from 15.44 MPa to 8.551 MPa, a decrease of 44.6%; the transverse shear stress CSHEAR1 increased from ±0.11 MPa to ±0.17 MPa, an increase of 50%; the absolute value of the longitudinal shear stress CSHEAR2 decreased from 5.40 MPa to 2.99 MPa, a decrease of 44.7%; the combined tangential force CSHEARF decreased from 4.128 × 10⁻⁶ MPa. 3 N decreased to 2.287 × 10 3 N decreased by 44.6%; the amplitude of lateral slip CSLIP1 decreased from 0.075mm to 0.050mm, a reduction of 33%; the longitudinal slip CSLIP2 reversed from being dominated by positive (+0.295~0.000mm) to being dominated by negative (+0.061~-0.273mm).
[0075] The wheel-rail contact mechanical performance evaluation method based on the pearlite to bainite volume ratio described in this invention further includes the following steps: S8: After step S7, determine the design criterion output step, i.e., when the engineering application requires stable contact mechanical properties, select... ≤50% or ≥85%, avoid 60%≤ The critical sensitivity range is ≤80%.
[0076] This invention is implemented using ABAQUS finite element software and employs Python scripts for parametric modeling and batch simulation calculations.
[0077] Figure 3 The image shows the three-dimensional geometry of the dumbbell-shaped uniaxial tensile specimen, including the clamping end 101, gauge length 102, and rounded transition region 103. White represents pearlite, and green represents bainite. The geometric design of the first finite element model of the dumbbell-shaped uniaxial tensile specimen meets the requirements of GB / T228.1-2021 standard. The length-to-diameter ratio of the gauge length 102 is approximately 2.3:1, which effectively avoids the influence of end effects on the stress state of the gauge length 102. The diameter of the clamping end 101 is larger than the diameter of the gauge length 102, ensuring that the specimen undergoes uniform deformation within the gauge length 102 during tensile testing rather than fracture at the clamping end 101. When building the three-dimensional solid model of the specimen in ABAQUS / CAE, a finer mesh is used for the gauge length 102, while a coarser mesh is used for the rounded transition region 103 and the clamping end 101. This combination of dense and sparse meshing strategies can control the total number of elements while ensuring computational accuracy.
[0078] Figure 4 , Figure 5 The three-dimensional finite element model of wheel-rail contact shown here fully displays all components including wheelset 201, frame 202, outer rail 203a, inner rail 203b, floating plate 204, fastener 205, primary suspension 206, grounding spring 207 and track bed 208.
[0079] Table 1 shows the equivalent elastic parameters for 11 groups of pearlite and bainite with different volume ratios.
[0080] Figure 6 , Figure 7 The figures show the stress-time and strain-time curves of the central node under different volume ratios in Embodiment 1 of the present invention. Figure 6 As shown, the stress at each volume ratio exhibits a linear increasing trend with time, with the stress in fully bainite being higher than that in fully pearlite. As the pearlite content increases, the stress response shows an overall decreasing trend, but the intermediate curves show local intersections, indicating it is not strictly monotonic. Figure 7 As shown, the strain response under different volume ratios is basically the same, and the curves have a high degree of overlap, indicating that the strain evolution law of each specimen is basically the same under the same loading conditions.
[0081] During the simulation, the ratio of kinetic energy to internal energy for each volume ratio was less than 5%, indicating that the loading rate setting was reasonable and met the quasi-static loading conditions. The equivalent stress at the center node of gauge length segment 102 was uniformly distributed along the axial direction, and the influence of edge effects was negligible, making the extracted stress-strain data representative. The stress-strain curve obtained from the tensile simulation showed a high degree of linearity, R... 2 The value is >0.9999, and the relative deviation between the fitted slope and the theoretical value is ≤0.01%. The peak stress at the center of gauge length 102 is 37.9~42.4MPa, accounting for only 6.5%~10.8% of the yield strength, and all working conditions are in the linear elastic stage.
[0082] Table 2 shows the maximum values of contact normal force CNORMF and contact normal stress CPRESS for 11 groups of pearlite to bainite with different volume ratios in Example 1 of the present invention.
[0083] Table 3 shows the contact tangential forces (including transverse shear stress CSHEAR1, longitudinal shear stress CSHEAR2, and combined tangential force CSHEARF) of 11 groups of pearlite to bainite with different volume ratios in Example 1 of the present invention.
[0084] Table 4 shows the contact slip (including transverse slip CSLIP1 and longitudinal slip CSLIP2) of 11 groups of pearlite and bainite with different volume ratios in Example 1 of the present invention.
[0085] Table 5 shows the equivalent friction coefficients for 11 groups of pearlite to bainite volumes with different ratios in Example 1 of the present invention. =CSHEARF max / CNORMF max The tables are as follows: Table 1. Equivalent elastic parameters of 11 groups of pearlite to bainite at different volume ratios.
[0086] Table 2. Maximum values of contact normal force (CNORMF) and contact normal stress (CPRESS) for 11 groups of pearlite to bainite volumes with different ratios.
[0087] Table 3. Contact tangential forces at different volume ratios of pearlite and bainite in 11 groups.
[0088] Table 4. Contact slip of 11 groups of pearlite and bainite at different volume ratios
[0089] Table 5. Equivalent friction coefficients for 11 groups of pearlite to bainite volumes with different ratios.
[0090] Wheel-rail contact response analysis: Substitute each set of parameters into the wheel-rail contact model (see Table 2), extract the contact normal force value (see Table 3), extract the contact tangential force value (see Table 4), and extract the contact slip value. From Tables 2, 3, and 4, it can be seen that when the pearlite volume fraction... When the pearlite volume fraction reaches 70%, all indicators show synchronous anomalies. This synchronous anomaly indicates that the contact mechanical properties of the material undergo a fundamental change when the pearlite volume fraction reaches 70%. The contact normal force and the combined tangential force decrease synchronously while maintaining a constant proportional relationship, indicating that the friction constitutive relationship remains unchanged, and the anomaly originates from changes in the material's own load-bearing capacity and deformation compatibility. The equivalent friction coefficient is 0.350~0.351 in all groups (see Table 5), indicating that the tangential force and normal force change synchronously, and the anomaly does not originate from a change in the friction constitutive model.
[0091] Figure 8 , Figure 9 , Figure 10 This is a CNORMF contour map of the contact normal force under three different pearlite contents in the experiments of this invention. Figure 11 , Figure 12 , Figure 13 This is a CPRESS contour plot of the contact normal stress of pearlite under three different contents in the experiment of this invention; Figure 8 , Figure 9 , Figure 10 , Figure 11 , Figure 12 , Figure 13The comparison cloud map shows that the contact area exhibits a uniform and symmetrical distribution when the pearlite content is 0% and the entire bainitic state is in effect, as well as when the pearlite content is 100% and the entire pearlite state is in effect. However, when the pearlite content reaches 70%, the normal load-bearing capacity of the contact area decreases significantly, and the distribution pattern becomes obviously distorted.
[0092] Figure 14 , Figure 15 , Figure 16 This is a CSHEAR1 contour plot showing the transverse shear stress of pearlite under three different content conditions in the experiments of this invention. Figure 17 , Figure 18 , Figure 19 This is a CSHEAR2 contour plot of the longitudinal shear stress of pearlite under three different contents in the experiments of this invention. Figure 20 , Figure 21 , Figure 22 This is a CSHEARF contour map of the synthetic tangential force of pearlite under three different content conditions in the experiment of this invention. Figure 14 , Figure 15 , Figure 16 , Figure 17 , Figure 18 , Figure 19 , Figure 20 , Figure 21 , Figure 22 The contrast contour plots were constructed. When the pearlite content was 70%, the amplitude of the transverse shear stress CSHEAR1 contour plot increased significantly, while the amplitudes of the longitudinal shear stress CSHEAR2 and the combined tangential force CSHEARF both contracted sharply, indicating that the anisotropy was amplified drastically in the critical state.
[0093] Figure 23 , Figure 24 , Figure 25 This is a CSLIP1 contour map showing the lateral slip of pearlite under three different content conditions in the experiments of this invention. Figure 26 , Figure 27 , Figure 28 This is a CSLIP2 contour map showing the longitudinal slip of pearlite under three different content conditions in the experiments of this invention. Figure 23 , Figure 24 , Figure 25 , Figure 26 , Figure 27 , Figure 28 The contrast cloud map is constructed. When the pearlite content is 70%, the amplitude of the lateral slip CSLIP1 decreases from about 0.075 mm to about 0.050 mm; the longitudinal slip CSLIP2 direction is reversed when the pearlite content is 70%, changing from positive dominance to negative dominance.
[0094] The following are the criteria for determining and designing critical intervals.
[0095] The effect of pearlite volume fraction on wheel-rail contact mechanical properties exhibits a three-stage characteristic: The three stages correspond to different microstructure evolution processes: In stage I, pearlite is distributed in the bainite matrix as isolated islands, the interface area between the two phases is small, and the degree of deformation incoordination is low; in stage II, the volume ratio of the two phases is close, forming a bicontinuous interwoven structure, the interface area reaches the maximum, and the degree of deformation incoordination is the highest; in stage III, bainite is distributed in the pearlite matrix as isolated islands, and the structure recovers to stability.
[0096] Stage I, Pearlite Volume Fraction ≤50%. As shown in Tables 2, 3, and 4, the contact normal force CNORMF stabilizes at 1.174 × 10⁻⁶. 4 ~1.179×10 4 Between N and N, the contact normal stress (CPRESS) stabilizes between 15.39 and 15.45 MPa, the transverse shear stress (CSHEAR1) is ±0.111 to ±0.114 MPa, the absolute value of the longitudinal shear stress (CSHEAR2) is 5.384 to 5.407 MPa, the transverse slip (CSLIP1) is ±0.073 to ±0.077 mm, and the longitudinal slip (CSLIP2) is predominantly positive, ranging from +0.273 to -0.059 mm to +0.295 to 0.000 mm. During this stage, pearlite is dispersed in the bainitic matrix as isolated particles, offering limited resistance to overall deformation. Stress concentration at the two-phase interface is low, and macroscopic contact properties remain stable.
[0097] Phase II, 60% ≤ ≤80%, This represents the volume fraction of pearlite. The volume ratios of the two phases are close, forming a bicontinuous interwoven structure. A sudden change occurs when the hard pearlite phase approaches the critical threshold for forming a continuous load-bearing framework. The lower-hardness bainite and the higher-hardness pearlite deform at different rates, leading to stress concentration at the phase interface. The two phases, due to their different deformation characteristics, restrain each other, hindering the coordinated deformation of the overall structure and reducing the macroscopic load-bearing capacity. Furthermore, the strong constraint of the pearlite framework on lateral deformation significantly increases shear stress, while the disruption of the continuous bainite network causes a substantial decrease in longitudinal load-bearing capacity. Once the pearlite skeleton reaches 80%, it becomes more complete and continuous, the structure regains a stable load transfer path, and its performance gradually recovers.
[0098] Stage III, Pearlite Volume Fraction ≥85%. As shown in Tables 2, 3, and 4, all indicators have recovered to the Stage I level. At this point, pearlite forms a continuous matrix, bainite is distributed in isolated island-like patterns, overall coordination is good, and contact mechanical properties are stable.
[0099] Based on the above mechanism analysis, when engineering applications require stable contact mechanical properties, the pearlite volume fraction should be satisfied. ≤50%, or ≥85%; avoid 60% ≤ The critical sensitivity range is ≤80%. The equivalent friction coefficient is independent of the pearlite content and requires interface engineering techniques such as surface treatment, lubrication, or texturing to achieve friction control. If finite element simulation is used for wheel-rail contact analysis, and 60% ≤ When the accuracy is ≤80%, it is recommended to introduce anisotropic constitutive models or multi-scale models.
[0100] Without departing from the concept of this invention, several modifications and improvements can be made, for example: ①The volume ratio of pearlite to bainite is not limited to 11 groups, and the number of groups can be increased or decreased according to the accuracy requirements.
[0101] ②The wheel-rail contact model is not limited to the above parameter configuration, and the model parameters can be adjusted according to the specific vehicle type and track conditions.
[0102] ③The evaluation method is not limited to ABAQUS software, but can also be implemented using other finite element software such as ANSYS and Marc.
[0103] ④ The constitutive model is not limited to an isotropic elastoplastic model; anisotropic yield criteria or multi-scale models may also be introduced to improve the simulation accuracy of the critical interval.
[0104] ⑤ The evaluation method described above can be further extended to the evaluation of contact mechanical properties of other two-phase or multi-phase material systems.
[0105] In summary, the embodiments of the present invention provide a method for evaluating the mechanical properties of wheel-rail contact based on the volume ratio of pearlite to bainite. After obtaining the microstructure parameters of the wheel-rail materials, it can quickly and accurately evaluate the influence of the microstructure on the mechanical properties of wheel-rail contact, solving the problem that the microstructure parameters of wheel-rail materials cannot be quickly correlated with the macroscopic mechanical properties of wheel-rail contact. This invention is applicable to component screening and constitutive parameter selection in finite element modeling during the wheel-rail material development stage. It is also applicable to the comparative evaluation of the mechanical properties of wheel-rail materials under different heat treatment processes. It provides a method for studying the correlation between the microstructure design and service performance optimization of rail materials. This method can also be used to analyze the differences in wheel-rail contact fatigue life under different pearlite to bainite volume ratios, providing a basis for extending the service life of rails.
Claims
1. A method for evaluating the mechanical properties of wheel-rail contact based on the volume ratio of pearlite to bainite, characterized in that, It includes the following steps: S1: For the pearlite and bainite in wheel and rail materials, set multiple sets of pearlite to bainite volume ratios; S2: Determine material parameters; S3: Calculate the equivalent elastic parameters for each group of volume ratios according to Voigt's constant strain mixing principle. The equivalent elastic parameters include the equivalent elastic modulus. and equivalent Poisson ratio ; S4: Establish a finite element model of the dumbbell-shaped uniaxial tensile specimen and perform tensile simulation verification: Assign the equivalent elastic parameters under each volume ratio obtained in step S3 to the first model, and obtain the stress-strain curves under each volume ratio; extract the data from the stress-strain curves and perform linear fitting to obtain the simulated values of the equivalent elastic modulus under each volume ratio, and compare each simulated value of the equivalent elastic modulus with the corresponding equivalent elastic modulus in step S3. If the relative deviation from the theoretical value is ≤X, proceed to the next step; otherwise, return to check the parameters and model settings and re-verify. S5: Establish a three-dimensional finite element model of wheel-rail contact; assign the simulated equivalent elastic modulus values of each group of volume ratios compared in step S4 and the plastic parameters determined by linear interpolation according to the hybrid rule to the rail material in the finite element model; perform wheel-rail contact simulation; S6: Extract the mechanical response parameters on the wheel-rail contact interface and obtain the variation characteristics of each mechanical response parameter with the pearlite volume fraction; S7: Based on the variation characteristics of each mechanical response parameter with the pearlite volume fraction, determine the evolution stage of wheel-rail contact mechanical properties: when Performance is stable when ≤50%; when 60%≤ Performance changes drastically when ≤80%; Performance stabilizes when ≥85% is achieved; This represents the volume fraction of pearlite.
2. The method for evaluating the mechanical properties of wheel-rail contact based on the volume ratio of pearlite to bainite according to claim 1, characterized in that, In step S1, 11 sets of pearlite to bainite volume ratios are set, and these 11 sets of pearlite to bainite volume ratios are: 0∶10, 1∶9, 2∶8, 3∶7, 4∶6, 5∶5, 6∶4, 7∶3, 8∶2, 9∶1, 10∶0.
3. The method for evaluating the mechanical properties of wheel-rail contact based on the volume ratio of pearlite to bainite according to claim 1, characterized in that, In step S2, the material parameters include the elastic modulus of pearlite. Pearl Poisson's ratio bainitic elastic modulus Bausch's Poisson's ratio .
4. The method for evaluating the mechanical properties of wheel-rail contact based on the volume ratio of pearlite to bainite according to claim 3, characterized in that, In step S3, the equivalent elastic modulus and equivalent Poisson ratio The calculation formula is: (1), (2), in, This represents the volume fraction of pearlite. is the volume fraction of bainite, and .
5. The method for evaluating the mechanical properties of wheel-rail contact based on the volume ratio of pearlite to bainite according to claim 1, characterized in that, In step S4, the method for extracting the data from the stress-strain curve and performing linear fitting to obtain the equivalent elastic modulus simulation values for each group of volume ratios is to use a displacement loading method to fix the lower end face of the specimen, apply a tensile load with a total displacement of 12 mm and a loading rate of 2 mm / min along the axial direction on the upper end face of the specimen, extract the stress-strain data of the center node of the gauge segment (102) in the stress-strain curve and perform linear fitting to obtain the equivalent elastic modulus simulation values for each group of volume ratios.
6. The method for evaluating the mechanical properties of wheel-rail contact based on the volume ratio of pearlite to bainite according to claim 1, characterized in that, In step S4, X = 0.01%.
7. The method for evaluating the mechanical properties of wheel-rail contact based on the volume ratio of pearlite to bainite according to claim 1, characterized in that, In step S5, the three-dimensional finite element model of wheel-rail contact includes wheelset (201), frame (202), outer rail (203a), inner rail (203b), floating plate (204), fastener (205), primary suspension (206), grounding spring (207) and track bed (208). The wheelset (201) consists of outer wheel (201a), inner wheel (201b) and axle (201c). The outer rail (203a) and inner rail (203b) are two steel rails. The method for simulating wheel-rail contact is to take the surface of the outer wheel (201a) and the surface of the inner wheel (201b) as the main surface, and the surface of the outer rail (203a) and the surface of the inner rail (203b) as the secondary surface. The finite slip formula is used, the normal contact behavior is close contact, the tangential behavior adopts the penalty function friction formula, and the friction coefficient is 0.
35.
8. The method for evaluating the mechanical properties of wheel-rail contact based on the volume ratio of pearlite to bainite according to claim 1, characterized in that, In step S6, the mechanical response parameters include contact normal force CNORMF, contact normal stress CPRESS, transverse shear stress CSHEAR1, longitudinal shear stress CSHEAR2, combined tangential force CSHEARF, transverse slip CSLIP1, and longitudinal slip CSLIP2; and the equivalent coefficient of friction for each group of volume ratios. =CSHEARF max / CNORMF max All are within the range of 0.350 to 0.
351.
9. The method for evaluating the mechanical properties of wheel-rail contact based on the volume ratio of pearlite to bainite according to claim 8, characterized in that, In step S7, the sudden change in performance is manifested as follows: At 70%, the contact normal force CNORMF decreases; the contact normal stress CPRESS decreases; the transverse shear stress CSHEAR1 increases; the absolute value of the longitudinal shear stress CSHEAR2 decreases; the combined tangential force CSHEARF decreases; the amplitude of transverse slip CSLIP1 decreases; and the longitudinal slip CSLIP2 reverses from being dominated by the positive direction to being dominated by the negative direction.
10. The method for evaluating the mechanical properties of wheel-rail contact based on the volume ratio of pearlite to bainite according to claim 1, characterized in that, It also includes the following steps: S8: After step S7, determine the design criterion output step, i.e., when the engineering application requires stable contact mechanical properties, select... ≤50% or ≥85%, avoid 60%≤ The critical sensitivity range is ≤80%. This represents the volume fraction of pearlite.
Citation Information
Patent Citations
Method for evaluating wheel-rail contact state based on logistic regression
CN121682157A
